DAMPAK PERUBAHAN TUTUPAN LAHAN PERTANIAN TERHADAP INDEKS KETAHAN PANGAN & INDEKS PEMBANGUNAN MANUSIA PULAU LOMBOK - Reza yudi candrra; Susanti, Febrita (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2026)
Pulau Lombok experienced significant land-cover changes during the 2020–2024 period based on NDVI analysis, which revealed an approximate 6.52% decrease in vegetated areas. This decline occurred mainly in dense vegetation zones, while non-vegetated and built-up areas increased due to development pressures and urban expansion. Such transformations have the potential to affect environmental sustainability and reduce the availability of productive agricultural land. Regression analysis produced an Adjusted R² value of 0.520, indicating that changes in agricultural land area have a moderately strong influence on variations in the Food Security Index (IKP) and the Human Development Index (HDI). IKP tends to decline in regions with more intensive land conversion, whereas HDI increases alongside infrastructure growth and economic development. These findings highlight a clear trade-off between socio-economic progress and environmental sustainability, emphasizing the need for more adaptive and sustainable land management strategies to maintain balanced development across Pulau Lombok.